Analysis of Management Aspects of UMKM Denata Laundry in Perum Surya Residence, Damarsi Village, Sidoarjo Regency - Nanda Alfreda Putri; Abdur Rohman (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
Most small and medium entrepreneurs face limitations regarding capital, human resources, information and technology. UMKM have many workers and have great potential to absorb labor. Laundry is an industry that has developed quite rapidly in recent years. Competition in the laundry business in Indonesia is increasing, this is indicated by the increasing number of manufacturers involved in fulfilling customer needs and desires. Everyone doesn't have much free time because life routines are getting busier. One of the Denata Laundry businesses is in Sidoarjo Regency and already has several employees, and the business is considered to be growing rapidly. Denata Laundry also provides free clothes pick-up and drop-off services with no additional fees. Clean and neat packaging of clothes. Of course, apart from its advantages, this business also has many business competitors. Challenges and risks also often arise in the Denata Laundry business. The purpose of this research is to determine the feasibility of the Denata Laundry business in terms of management aspects, whether it is feasible/not feasible. Judging from the research results, the Denata Laundry business is feasible because the management aspect is well structured and the operations are clear. This research is a descriptive type of research with a qualitative approach. Data collection methods were carried out by means of interviews, observation and documentation.